2006
DOI: 10.1002/lt.20640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ischemic preconditioning in whole liver transplantation from deceased donors. A pilot study

Abstract: The effect of ischemic preconditioning (IPC) in orthotopic liver transplantation (OLT) has not yet been clarified. We performed a pilot study to evaluate the effects of IPC in OLT by comparing the outcomes of recipients of grafts from deceased donors randomly assigned to receive (IPCϩ group, n ϭ 23) or not (IPCϪ group, n ϭ 24) IPC (10-min ischemia ϩ 15-min reperfusion). In 10 cases in the IPCϩ group and in 12 in the IPCϪ group, the expression of inducible nitric oxide synthase (iNOS), neutrophil infiltration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
5

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 39 publications
(70 reference statements)
3
60
1
5
Order By: Relevance
“…In the third trial, a pilot study of 47 liver recipients, Cescon et al showed that 10 min IPC decreased biochemical RP injury. However, clinical outcomes including initial poor function, graft nonfunction and graft and patient survival were similar between the IPC and No IPC groups (19).…”
Section: Koneru Et Almentioning
confidence: 83%
See 2 more Smart Citations
“…In the third trial, a pilot study of 47 liver recipients, Cescon et al showed that 10 min IPC decreased biochemical RP injury. However, clinical outcomes including initial poor function, graft nonfunction and graft and patient survival were similar between the IPC and No IPC groups (19).…”
Section: Koneru Et Almentioning
confidence: 83%
“…We concluded that longer periods of IPC might be more effective (17). Two other groups published conflicting results of prospective randomized studies of 10 min of IPC in DDLT (18,19).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…67,68 The fact that liver IPC in deceased donors reduces RP injury in some studies shows that IPC is inducible in the presence of brain death. 27 Additional studies of IPC of the liver and other organs in brain-dead animals are needed to fill the knowledge gaps. A summary of the potential reasons for the observed disparity between the bench and bedside is provided in Table 4.…”
Section: Brain Death and Associated Pathophysiologymentioning
confidence: 99%
“…Azoulay et al [212] found that although IPC protected cadaveric liver grafts against IRI, this beneficial effect was counter-balanced by decreased early graft function. Cescon and colleagues demonstrated similar protective effects against IRI, but IPC showed no clinical benefit (primary graft function and survival rates) in liver transplantation from deceased donors [213] . Although gaining popularity, the incongruous evidence of the clinical effects of IPC has precluded its widespread adoption in liver transplantation units.…”
Section: Clinical Implications Of Ischaemic Preconditioning In Liver mentioning
confidence: 98%